Petrogenesis and geodynamic environment of the Recent pyroclastic deposits from Baïgom and Petpenoun volcanoes of the Noun Plain, Cameroon Volcanic Line, Central Africa - Luc Achille Ziem A Bidias; Mekala Ram Mohan; N.V. Chalapathi Rao; Amidou Moundi (Geosystems and Geoenvironment, 2023)
This study presents petrography, mineral chemistry, whole-rock major and trace elemental systematics for Recent pyroclastic deposits from volcanic edifices of Baïgom and Petpenoun, located in the Noun Plain graben along the Cameroon Volcanic Line (CVL), Central Africa, to better understanding their petrogenesis and geodynamic environment. The samples are mainly ash, lapilli and scoria, belonging to two different magmatic series: an alkaline series and a sub-alkaline series. Petrographic and mineralogical evidence in alkaline samples show a common crystallizing mineral assemblage of olivine, clinopyroxene and/or plagioclase, scattered in a fine-grained to glassy matrix. Clinopyroxene occurs in variable sizes, and includes megacrysts, which show either little or strong zonation, and thus represent different processes. The large, unzoned crystals provide clear evidence for prolonged magma chamber processes involving high and near-constant melt/Clinopyroxene ratios. The megacryst abundances are interpreted as crystal accumulation. The thermobarometry results in alkaline samples provide temperatures of 1188–1267 °C and pressure estimates in the range of 10.3–23.8 kbar. All the Recent pyroclastic deposits display high (La/Yb)N (11.20–20.35) and (Tb/Yb)N ratios (1.93–2.64), suggesting that their parental magmas originated from partial melting in the garnet-bearing mantle zone, at a depth > 80 km. The near-constant Ce/Y (3.14–3.76) and the higher Zr/Nb (5.85–10.71) ratios in sub-alkaline lava samples adequately fit with derivation of the magmas from a melt column extending across the garnet-spinel transition zone. Our results suggest two distinct origins for Recent pyroclastic samples from volcanic edifices of Baïgom and Petpenoun and imply an underlying heterogeneous mantle source beneath the CVL.